Gas measurements from the Costa Rica–Nicaragua volcanic segment suggest possible along-arc variations in volcanic gas chemistry - Aiuppa, A. (2014)
Obtaining accurate estimates of the CO2output from arc volcanism requires a precise understanding of the potential along-arc variations in volcanic gas chemistry, and ultimately of the magmatic gas signature of each individual arc segment. In an attempt to more fully constrain the magmatic gas signature of the Central America Volcanic Arc (CAVA), we present here the results of a volcanic gas survey performed during March and April 2013 at five degassing volcanoes within the Costa Rica–Nicaragua volcanic segment (CNVS). Observations of the volcanic gas plume made with a multicomponent gas analyzer system (Multi-GAS) have allowed characterization of the CO2/SO2-ratio signature of the plumes at Poás (0.30 ±0.06, mean ±SD), Rincón de la Vieja (27.0 ±15.3), and Turrialba (2.2 ±0.8) in Costa Rica, and at Telica (3.0 ±0.9) and San Cristóbal (4.2 ±1.3) in Nicaragua (all ratios on molar basis). By scaling these plume compositions to simultaneously measured SO2fluxes, we estimate that the CO2outputs at CNVS volcanoes range from low (25.5 ±11.0tons/day at Poás) to moderate (918 to 1270 tons/day at Turrialba). These results add a newinformation to the still fragmentary volcanic CO2output data set, and allow estimating the total CO2output from the CNVS at 2835 ±1364tons/day. Our novel results, with previously available information about gas emissions in Central America, are suggestive of distinct volcanic gas CO2/ST(=SO2+H2S)-ratio signature for magmatic volatiles in Nicaragua (∼3) relative to Costa Rica (∼0.5–1.0). We also provide additional evidence for the earlier theory relating the CO2-richer signature of Nicaragua volcanism to increased contributions from slab-derived fluids, relative to more-MORB-like volcanism in Costa Rica. The sizeable along-arc variations in magmatic gas chemistry that the present study has suggested indicate that additional gas observations are urgently needed to more-precisely confine the volcanic CO2from the CAVA, and from global arc volcanism.